EKSEKUSI PUTUSAN HAKIM TERHADAP OBJEK HAK TANGGUNGAN YANG TELAH DILAKUKAN CESSIE - Thorico Monada; Achmad Jaka Santos Adiwijaya; Ujang Bahar (JURNAL ILMIAH LIVING LAW, 2021)
The purpose of this research is to: 1) Know how the execution of the mortgage right that has been carried out by cessie which in the process is filed a rebuttal in the district court by the parties, 2) Knowing how to resolve the execution case No. 15 / Pdt / Eks.Akte / 2003 / PN.Bgr in relation to rebuttal No. 59 / Pdt.Bth / 2005 / PN.Bgr. This research method is a normative juridical approach. The normative juridical research stage uses literature study. The results of this research are: 1) The execution of the auction conducted by the Bogor District Court is canceled by the Office of the State Wealth and Auction Service (KPKNL) because the cessie transfer process is not registered at the National Land Agency Office (BPN). 2) An Execution Petitioner must withdraw his application for execution and register a cessie at the Land Office and submit a re-application.